The significance of ant-hills in depressed areas of the Great Chaco - Pire, Eduardo F; Torres, Patricia S; Romagnoli, Ornar D; Lewis, Juan P (Revista de Biología Tropical, 1991)
Ant-hills of Camponotus punctulatus (Mayr.) are common in Chaquenian depressed areas. We studied density, spatial distribution, shape and size of ant-hills in the Submeridional Lowlands of the Chaco. As an average there are 500 ant-hills/Ha that are conical mounds 0.62 m high covered with vegetation. Their density increases in relatively high soils, they are taller the lowest the soíl, and tend to be uniformly distributed. They seem to be a flood escape mechanism of the ant colony, and are a major disturbance that has an effect on vegetation pattem and floristic richness